2014
DOI: 10.1155/2014/369713
|View full text |Cite
|
Sign up to set email alerts
|

A New Optimal Eighth-Order Ostrowski-Type Family of Iterative Methods for Solving Nonlinear Equations

Abstract: Based on Ostrowski's method, a new family of eighth-order iterative methods for solving nonlinear equations by using weight function methods is presented. Per iteration the new methods require three evaluations of the function and one evaluation of its first derivative. Therefore, this family of methods has the efficiency index which equals 1.682. Kung and Traub conjectured that a multipoint iteration without memory based on n evaluations could achieve optimal convergence order 2n−1. Thus, we provide a new cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Per iteration, the present methods require four function evaluations and therefore have the efficiency index equal to 1.682. This method has less number of weight functions which is a significant contribution when compared to a similar method found in [8]. Some of the proposed methods were also compared for their performance and efficiency with various other iteration methods of the same order and it was found that the new class of method produces better numerical results.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Per iteration, the present methods require four function evaluations and therefore have the efficiency index equal to 1.682. This method has less number of weight functions which is a significant contribution when compared to a similar method found in [8]. Some of the proposed methods were also compared for their performance and efficiency with various other iteration methods of the same order and it was found that the new class of method produces better numerical results.…”
Section: Resultsmentioning
confidence: 98%
“…Thus the optimal order for three evaluations per iteration would be four, four evaluations per iteration would be eight and so on. Recently, some fourth and eighth order optimal iterative methods have been developed using weight functions (see [1,4,5,7,8,10,11,12,13,14] and references therein). A more extensive list of references as well as a survey on the progress made in the class of multi-point methods is found in the recent book by Petkovic et al [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, based on this new class of methods, we present an efficient class of multipoint methods with memory by suitable variation of a free parameter in each iterative step in Section 3. Numerical examples show better performance of our method than the Lotfi and Eftekhari's method (2), Kung and Traub's method (3), Thukral's method (4), and Eftekhari's method (5) in Section 4. Section 5 is a short conclusion.…”
Section: Introductionmentioning
confidence: 92%
“…Cordero et al in [1] extended the approaches of Zheng et al to provide a novel class of iterative methods with memory that use self-accelerating parameters calculated by Newton's interpolation with divided differences. In [5], a new family of optimal eighth-order Ostrowski-type iterative methods by using the method of weight functions has been derived by Lotfi and Eftekhari, which is written as:…”
Section: Introductionmentioning
confidence: 99%